To find the quadratic equation in intercept form that meets the given conditions, we can start by using the x-intercepts. The intercept form of a quadratic equation with given x-intercepts \( x_1 \) and \( x_2 \) is:
\[ y = a(x - x_1)(x - x_2) \]
Given the x-intercepts at \( (2,0) \) and \( (4,0) \), we can write:
\[ y = a(x - 2)(x - 4) \]
Next, we need to determine the value of \( a \) using the third point \( (5, 6) \). We substitute \( (x, y) = (5, 6) \) into the equation:
\[ 6 = a(5 - 2)(5 - 4) \]
This simplifies to:
\[ 6 = a(3)(1) \] \[ 6 = 3a \] \[ a = 2 \]
Now substitute \( a = 2 \) back into the equation:
\[ y = 2(x - 2)(x - 4) \]
This is the quadratic equation in intercept form that accurately represents the information given.
Therefore, the correct response is:
y = 2(x−2)(x−4)